Delayed Tamponade after Traumatic Wound with Left Ventricular Compression - Fahad Almehmadi; Mark Chandy; Kim A. Connelly; Jeremy Edwards (Case Reports in Cardiology)
Delayed cardiac tamponade after a penetrating chest injury is a rare complication. The clinical diagnosis of tamponade is facilitated with imaging. We present a case report of a 23-year-old male who was brought to emergency after multiple stab wounds to the chest. After resuscitation and repair of laceration of right internal mammary artery and right ventricle, he was discharged but later returned with shortness of breath. Echocardiography revealed a rare case of delayed pericardial tamponade causing left ventricular collapse. The pericardial effusion was treated with emergent pericardiocentesis and later required a thoracoscopy guided pericardial window for definitive management.